Impact Behaviour of Existing Bicycle Helmet Subjected to Drop Test - Mohd Nawi, Mohamad Irfan Farhan; Ibrahim @ Tamrin, Mohd Norihan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
A bicycle helmet is a crucial piece of safety equipment that serves to protect the head from injury during accidents. In this research, the focus is on investigating the deformation behavior and impact capability of commuter bicycle helmets with and without liners using Finite Element Analysis (FEA). Based on actual measurements, two commuter helmet models with a shell thickness of 0.4 mm made of polycarbonate (PC) and an inner thickness of 25 mm made of Expanded Polystyrene (EPS) were created. The drop tests simulated a free fall from a height of 1.5 meter with a constant gravity acceleration of 9.81 m/s-2. The commuter helmet shell was examined in the first simulation run, while the drop test parameters for the helmet with an inner were run in the second simulation. Output parameters such as displacement, equivalent stress, and strain were analyzed. The simulated data from both commuter helmet models was compared to determine the differences, providing insights into the deformation behavior and impact capability of the bicycle helmets with and without liners This research aims to contribute to the understanding of bicycle helmet performance in drop tests and inform future designs and improvements in bicycle helmet technology.